Migraine and comorbid pain - A. S. Zenkevich; E. G. Filatova; N. V. Latysheva (Медицинский совет, 2016)
A study to evaluate the prevalence of various pain syndromes (PS) in patients with chronic and episodic migraine and their potential pathogenetic relationship was carried out. The study involved 61 patients with chronic migraine (CM) and 42 patients with episodic migraine (EM) according to ICD revision 3. Patients with CM demonstrated a higher incidence of various pain syndromes compared with EM patients. The pain syndromes were dominated by temporomandibular joint dysfunction (TMJD) and neck pain. The correlation between the decrease in the daily activity of patients and the number of PS is demonstrated: working disability in migraine patients grows along with the increase in the number of comorbid pain syndromes. The authors concluded that dysfunctional changes in pain experienced by patients due to migraine chronicity create the conditions for occurrence of comorbid pain syndromes which are located primarily in the area of innervation of the trigemino-cervical complex. The fact that problems in everyday activity of patients with migraine are caused by migraine as the primary disease and by comorbid PS should be considered in the process of treatment.